Implications for the United States of the May 2008 draft agricultural modalities - Blandford, David; Laborde Debucquet, David; Martin, Will (International Centre for Trade and Sustainable Development, 2008)
The May 2008 draft agricultural modalities (WTO 2008) are the result of seven years of hard negotiations. Their structure, if not every detail, seems likely to be the basis for final proposals that must either be ratified or rejected by governments. The modalities cover the three pillars of domestic support, market access, and export competition. In this paper we examine their implications for the United States. The imposition of additional WTO disciplines on domestic support is a major issue for the United States. Higher world prices for major export commodities have reduced the amount of support provided to U.S. farmers in recent years but the long drawn-out process of concluding a new Farm Bill reflects the continued political importance of farm programs. Analysis of the most ambitious provisions of the draft modalities suggests that if a relatively high price environment continues the United States will be able to adapt to the new WTO domestic support commitments by making modest adjustments in its domestic policies. There are issues with a limited number of commodities. Cotton poses problems for meeting product specific bindings on AMS and blue box support and sugar pose problems for meeting product specific AMS commitments. These could be addressed by changing support programs in order to reduce notified support. Changes in the definition of the dairy support program in the 2008 Farm Act, which do not imply any fundamental change in the way the program actually operates, will reduce notified support for dairy. It is possible that other procedural changes could be made to reduce notified support for other commodities, for example, sugar. The strengthened disciplines on domestic support would have the effect of squeezing out a lot of the “water” in the amount of support that the United States can provide to U.S. farmers and stay within its WTO commitments. The United States would still have the option of changing the composition of support – expanding the use of the green box and making use of non product-specific support up to the limit imposed by de minimis and the overall OTDS binding. Nevertheless, significant reductions in the OTDS and the total AMS severely constrain the room for manoeuvre for support that is most closely linked to prices. However, if the optimistic price environment assumed by the U.S. Department of Agriculture does not materialize, limits on the total AMS and some product-specific AMS limits could well be exceeded unless alternatives to current support policies were found With respect to market access, while U.S. agricultural tariffs are relatively low on average there are some high tariffs on products such as sugar, meats, dairy products and beverages and tobacco. The relatively low tariff average means that around 90 percent of the tariff lines fall in the first band of the proposed tariff-cutting formula in the draft modalities, and hence are subject to the lowest proposed reductions. Despite this, the cuts in agricultural tariffs resulting from application of the formula are relatively substantial, with the trade weighted average MFN applied rate falling from 8 percent to 3.5 percent. Application of the proposed tariff escalation formula has virtually no impact on the average tariff, while application of the tropical products formula would reduce the post-round tariff from 3.5 percent to 3.2 percent with the largest impact on sugar, dairy products and tobacco. The sensitive product option is likely to have a relatively small impact on U.S. tariffs. With respect to market access for the United States, we find that the proposed tariff formulas in the modalities would sharply reduce average tariffs facing U.S. exports – from 14 percent to 8.7 percent. Most of this reduction comes from a sharp fall in the tariffs applied by other industrial countries. The provisions of the tariff formula for developing countries; the higher binding overhang; and lower initial rates of applied protection imply a much smaller reduction in the tariffs facing U.S. exports in developing countries. The sensitive product provisions reduce by half the reduction in the average tariff facing US exporters in other developed markets and, combined with special products, mean that applied tariffs faced by US exporters in developing countries decline very little. The elimination of export subsidies used by other countries (particularly, the European Union) has been a major U.S. objective in the current round of WTO negotiations. This would require the elimination of the one remaining export subsidy program for dairy products (DEIP) that has not been active in recent years. The draft modalities would also require changes in U.S. export credit programs, but these have already been modified to bring interest rates in line with those charged by commercial lenders. In addition, the intermediate export credit program (GSM 103) was eliminated in the 2008 Farm Act. Some additional modifications in financing terms for the remaining program (GSM 102) would probably be required to ensure full cost recovery Activity under U.S. food aid programs has been declining in recent years. The draft modalities foresee reduced emphasis on the provision of in-kind aid. The 2008 Farm Act contains some limited provisions for sourcing aid through local purchases of food in developing countries. However, a more general move in that direction can be expected to result in less support for food aid programs among farm groups and increasing difficulties in obtaining Congressional appropriations for food aid programs.